Inflexibility in organizational decision-making - Carrasco, Guillermo; Angeles, Adrianela; Marroquin-Tovar, Edmundo (Journal of Business Economics and Management, 2016)
The main objective of this investigation is to validate a measurement model that identifies the dimensions of inflexibility in organizational decision-making. For this purpose a Confirmatory Factor Analysis was conducted to assess how well the measured variables represent the constructs, which according to several authors of the literature, have been identified as limitations to organizational decision-making. In this study they were classified in three dimensions: limitations on Strategic Management, limitations on Human Resource Management and limitations on Financial Management.The analysis is based on data collected from 229 Mexican companies. The results show that the proposed model is a good measure of inflexibility in decision-making of these organizations. In addition, it was identified that the variable that best predicts the limitations in strategic management is the lack of clear objectives. Furthermore, it was found that the strongest predictor of limitations on human resources management is the presence of conflicts between employees; and regarding limitations on financial management, the best predictor is the falling profits of the organization. It is expected that this model will help organizations to identify and eliminate these limitations that constraint the organizational decision-making, facilitating their capability to adapt to the changing environment.